Pemetaan Kompetensi Teknis pada Beberapa Jabatan Berdasarkan Job Description di PT. X - Louis Kidhanny; Herri Christian Palit (Jurnal Titra, 2022)
PT. X is a company that produces cigarette filters and is under a holding company. As the company grows, more company management is needed for the continuity of the company. PT. X does not yet have a technical competency mapping on each task based on the job description of several positions held. Mapping is done to determine the technical competence of each position studied. The mapping of technical competence also determines the measurement method and target competency level. The positions to be studied are production supervisor, production assistant supervisor, logistic supervisor, logistic assistant supervisor, and logistic forklift driver. the method used in mapping is interview. The method used in the knowledge competency measurement method is a written test and oral test, the skill competency measurement method uses on the job training (OJT) and simulation and role play, the awareness competency measurement method uses a written test. The results of the research are in the form of technician competency mapping along with measurement methods and target levels for each task.